2010
DOI: 10.1248/bpb.33.289
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in Vitro Peyer's Patch Cell Culture System Correlative to in Vivo Study Using Intestine and Screening of Lactic Acid Bacteria Enhancing Intestinal Immunity

Abstract: Some lactic acid bacteria (LAB) function as probiotics. The beneficial functions brought by LAB on gastrointestinal conditions, such as constipation, diarrhea, inflammatory bowel disease, Helicobacter pylori infection, lactose intolerance, and colon cancer, have been reported. 1,2) LAB have also been found to modulate systemic and/or intestinal immune responses, including allergies, [3][4][5][6][7][8][9][10] although their application in medical treatment is still far from possible. It is important to accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We have previously shown that SN13T had significant capacity to enhance immune responses and to improve gastrointestinal conditions and liver function [6], [7]. In this study, however, a newly isolated LAB, Pediococcus pentosaceus LP28, was demonstrated to be a potent anti-obesity probiotic, in contrast to the SN13T.…”
Section: Discussionmentioning
confidence: 58%
“…We have previously shown that SN13T had significant capacity to enhance immune responses and to improve gastrointestinal conditions and liver function [6], [7]. In this study, however, a newly isolated LAB, Pediococcus pentosaceus LP28, was demonstrated to be a potent anti-obesity probiotic, in contrast to the SN13T.…”
Section: Discussionmentioning
confidence: 58%
“…We have demonstrated that some strains stocked in the LAB library are useful for enhancing intestinal immunity, improving liver function, and preventing metabolic syndrome. [3][4][5][6] LAB fermentation often proceeds even at low temperatures, causing the overgrowth of LABs. As the result, the degradation of flavors is proceeded and affected with taste of the fermented foods.…”
Section: )mentioning
confidence: 99%
“…Peyer's patch cells (PP-cells) was isolated from BALB/c mice and co-cultured with Lactobacillus according method of Jin et al [25] and [24]. Briefly, in each well 1.4×10 6 PP-cells was co-cultured with 1 or 10 µg/mL UV killed Lactobacillus for 15 h, the supernatant were then assessed using an enzyme-linked immunosorbent assay (ELISA) kit for IL -6, IL-10, IL-12p70 and TNF-α according to the manufacturer's instructions.…”
Section: Peyer's Patches Cell Isolation and Co-culture With Lactobacillimentioning
confidence: 99%